Does Gender Diversity in the Boardroom Improve Firm Performance? Evidence from Indonesia - Pasaribu, Pananda (UI Scholars Hub, 2019)
This study investigates board gender diversity in Indonesia's listed firms and its effect on firm performance from 2011-2016. After addressing the endogeneity of diversity, the results in this paper show that the proportion of female in the boardroom marginally improve firm performance. Firms with two or more female in the boardroom have a stronger impact on firm performance than firms with one female in the boardroom, consistent with the critical mass effect. Finally, certain sectors will gain more benefits of appointing females in the boardroom. The results suggest that increasing gender diversity in the boardrooms can have beneficial effects on firm performance, but the benefits may be subject to the critical mass and firm industry.